The Relationship between Learning Motivation, Student Worksheets, and Learning Outcomes in Computer and Network Engineering Education - Inneke Fortuna Irawan; Efrizon; Vera Irma Delianti; Rizkayeni Marta (Universitas Negeri Padang, 2025)
This study investigates the influence of learning motivation and student worksheets (LKPD) on students’ academic achievement in the subject of Computer and Network Engineering at a vocational high school. The research was motivated by the observation that student learning outcomes remained in the moderate category, potentially due to insufficient motivation and suboptimal use of instructional materials. This study aimed to (1) examine the relationship between learning motivation and learning outcomes, (2) analyze the relationship between LKPD and learning outcomes, and (3) assess the combined effect of learning motivation and LKPD on student achievement. A quantitative approach with a descriptive correlational design was employed, involving 36 Grade XI students in the Computer and Network Engineering program. Data were collected through validated questionnaires and documented mid-semester exam scores. The findings revealed a strong and statistically significant correlation between learning motivation and learning outcomes (r = 0.713, R² = 0.509), a moderate but significant relationship between LKPD and learning outcomes (r = 0.338, R² = 0.114), and a strong combined relationship between learning motivation and LKPD with learning outcomes (r = 0.716, R² = 0.513). These results highlight the critical role of both psychological and instructional factors in shaping academic performance in vocational education.